Parameter Optimization In 3D Printer Recycle Machine - Mat, Shafizal; Ramli, Faiz Redza; Alkahari, Mohd Rizal; Mustafar, Ahmad Al Idrisi; Zainal Aris, Muhamad Aminur 'Ilman; Jamli, Mohamad Ridzuan; Case, Keith (Asian Research Publishing Network, 2020)
3D printing technology has evolved rapidly to becoming one of the most postulate method in manufacturing process. Commonly, standard manufacturing process which is subtractive that produces a lot of waste opposite to 3D printing technology is way friendly to the environment. The idea of this application additive manufacturing method in 3D printing leads to less or no wasted materials and consumption of plastic materials has significantly increased due to high demand in market. However, the plastic waste products from the 3D printing still undergo significant increase due to the problem in every human-made creation. In order to minimize the negative impact of plastic waste to the environment, a machine of recycle 3D printing has been made and study on parameter optimization on 3D printer recycle machine have been done. The study used Minitab software to analyze the factor of parameter of 3D printing recycle machine. Taguchi method was used to suggest some experiments to be performed and provides an optimal value for each parameter that needs to be optimized in the operation of extruding. Analysis of extruded filament was conducted for every 30cm with minimum of three repetitions. In comparison of the new extruding filament and original filament show that some minor difference of the mechanical properties by using tensile test method. Percentage of error for diameter of filament indicates that 1.77mm diameter with 1.14% as the lowest error while diameter of 1.82mm with 4.00% as the highest error. This shows that 3D printer recycle machine has been optimized with the percentage of error below than 5% and it could be further improved in order to help in minimizing the negative impact of plastic wastes to the environment.